Pregnancy and SARS - CoV - 2 vaccination: Unraveling the myths - Anita Yadav; Jyoti Baghel; Avinash Prakash; Rajneesh Rawat (Barpeta Obstetrics and Gynaecological Society, 2021)
The development and implementation of SARS- CoV- 2 vaccination programs seem to be the main weapon for tiding over the ongoing pandemic. Despite pregnant women being a vulnerable group, they have been excluded from the ongoing vaccination drive in India. Amidst the second wave of SARS- CoV- 2, vaccination should be extended to pregnant women too. This manuscript highlights various aspects of the available vaccines for pregnant women. It also depicts the need for counseling in pregnant women regarding the direct and indirect advantages of vaccination, while acknowledging the paucity of safety data. Thus, vaccines should not be withheld from pregnant women who make an informed choice.